Effect of Problem-Based Learning Model on Improving Student Learning Outcomes in the Classification of Living Things Material - Sari, Amelia; Lamangantjo, Chairunnisah J.; Supartin, Supartin; Paramata, Dewi Diana; Yusuf, Frida Maryati; Hermanto, I Made (Jurnal Pijar Mipa, 2025)
Learning outcomes are very important as a benchmark for success in the learning process. This study aims to determine the effect of the Problem-Based Learning (PBL) model on improving student learning outcomes in the material of classification of living things at SMP Negeri 1 Suwawa. The method used is Quasi-experimental with a pretest-posttest control group design. The sample consisted of two classes, namely class VII A as the experimental class and class VII C as the control class, which were selected by random sampling. The instrument used was a multiple-choice test of 15 questions. The pretest results showed an average learning outcome of students in the experimental class of 49.8 and the control class of 50.2. After learning, the posttest results increased to 84.3 for the experimental class and 72.1 for the control class. The N-gain value of the experimental class was in the medium-high category with an average of 0.68, while the control class was in the medium category with an average of 0.44. The t-test results showed t-table, namely 5.62 ˃ 2.00 (at a significance level of 0.05), which means that there is a significant difference between the learning outcomes of students using the PBL model and those using the Discovery Learning model. Thus, it can be concluded that the PBL model-based learning has a positive and significant influence on student learning outcomes in the material on the classification of living things.